Occurrence and antimicrobial resistance profile of Salmonella spp. In calves from the Mesoregion Sertaõ of Alagoas, Brazil - Vasconcelos, Artur Bibiano De [UNESP]; Andrade, Vitoria De; Moraes, Ana Carolina Izidoro De [UNESP]; Ramos, Elísia Maria Oliveira De Almeida; Silva, Andrezza Caroline Aragaõ Da; Francą, Danilo Alves De [UNESP]; Vasconcelos, Catarina Bibiano De; Okamoto, Adriano Sakai [UNESP]; Silva, Karla Patrícia Chaves Da (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2021)
The diarrhea in calves, caused by Salmonella spp., provocates serious economic damage to cattle farming. This study aimed was to verify the occurrence of diarrhea and the isolation of strains of Salmonella spp. in diarrheal feces of calves from farms located in the Sertaõ from the state of Alagoas municipalities, and to characterize the in vitro resistance profile of Salmonella spp. isolated against conventional antimicrobials. The study was carried out with 431 calves from 10 to 90 days old. Of the total number of animals evaluated, 111 presented a diarrhea table, being analysed 111 samples of diarrhoeal faeces. The samples were sown in enrichment broths and selective culture media and the phenotypic and molecular characterization were performed. Among the animals evaluated, 25.75% (111/431) had diarrhea. The presence of Salmonella spp. was evidenced in 13.33% (2/15) of the studied establishments. Have been isolated 2.71% (3/111) strains of Salmonella spp. and have all been shown to be resistant to Cefotaxime and sensitive to Ciprofloxacin, Gentamicin, Amoxicillin, Ampicillin and Norfloxacin. Salmonella spp. and other infectious agents associated with diarrhea were confirmed in calves in the Sertaõ Alagoas mesoregion. The antimicrobial potential of the tested drugs reinforces the importance of their responsible and judicious use in the treatment of Salmonellosis, not being indicated the antibiotic therapy with Cefotaxima. The treatment based on Gentamicin, Amoxicillin, Ampicillin, Ciprofloxacin and Norfloxacin in the treatment of these animals, is recommended.
Ocorrência de Salmonella spp. Em bezerros e perfil de resistência antimicrobiana na Mesorregiaõ do Sertaõ de Alagoas, Brasil
Keywords: Antibiogram; Cattle; Diarrhea; Enteropathogens; Salmonellosis